SIMULTANEOUS BILATERAL UPPER URINARY TRACT UROTHELIAL CARCINOMA (UTUC) WITH LEFT NEPHROURETERECTOMY AND RIGHT ILEOURETERAL REPLACEMENT: A CASE REPORT OF CURATIVE APPROACH - Effendi, Rudini; Hudaya, Syamsu; Wallad, Caesar Khairul (Indonesian Journal of Urology, 2024)
Objective: The report aims to present a rare bilateral UTUC focusing on diagnostic and surgical treatment to improve the survival rate of patients with bilateral UTUC. Case(s) Presentation: We present a case report of a 59-year-old male who came in with gross hematuria accompanied with clots. Laboratory reveals a decreased renal function, while CT shows a bilateral mass in both ureters and left renal pelvis without bladder involvement. The patient then underwent left nephroureterectomy and right ureterectomy. In Intraoperative we preserve the right kidney by evaluating the tumor margin using ultrasound and ureteroscopy and deciding to substitute a full-length ureter with ileum as a precaution for a safety margin. Later on the pathological examination shown high-grade invasive urothelial cell carcinoma on both sides with staging pT2N0M0. Six months after surgery patient is in an excellent condition; weight and karnofsky score improvement. The Baseline Creatinin level was decreased, whereas CT showed no residual tumor in the right urinary tract system. Discussion: This article presents a rare case of bilateral UTUC with staging pT2N0M0 that was successfully treated with multidisciplinary care of radical and reconstructive surgery without chemotherapy. Conclusion: Bilateral UTUC is a scarce case, even among all urologic malignancies. Preserving kidney function in these cases is a priority to reduce further morbidity for the patient. Keywords: Bilateral UTUC, nephroureterectomy, ileoureteral replacement.